Analysis of Non-Menopatic Patient Loyalty at Dr. Rm. Soedjarwadi Regional Mental Hospital, Central Java Province - Asril Aziz Rahmatullah; Sudarwati Sudarwati; Oong Ridhoi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of service quality, facilities, rates, location, and hospital image on the loyalty of non-mental patients at Dr. RM. Soedjarwadi Mental Hospital, Central Java Province. This study used a quantitative method with a survey approach. The study population was all non-mental patients who had received services at Dr. RM. Soedjarwadi Mental Hospital, Central Java Province, with the criteria of having received treatment at least twice. Data were collected using a questionnaire compiled based on the indicators of each research variable. Data analysis was conducted using multiple linear regression to determine the partial and simultaneous effects of independent variables on patient loyalty. The results showed that service quality, facilities, rates, location, and hospital image influenced the loyalty of non-mental patients. Simultaneously, these five variables contributed significantly to increasing patient loyalty. Service quality and hospital image were the factors that had the most dominant influence on patient loyalty. The findings of this study indicate that efforts to improve service quality, develop facilities, set appropriate rates, increase location accessibility, and strengthen the hospital image need to be a priority in the strategy for developing non-mental services at Dr. RM. Soedjarwadi Mental Hospital, Central Java Province.